INFLUENCE OF ETHANOL, ISOPROPYL MYRISTATE & PROPYLENE GLYCOL ON IN VITRO PERMEATION OF DIMENHYDRINATE FROM TRANSDERMAL GEL - Sadaf Hayat Laghari; Imran Suheryani; Abdullah Dayo; Komal Zaman; Raheela Saleem; Nimra Zaman; Ubed-Ur-Rehman; Syed Zohaib Hussain; Jabbar Abbas (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Carbopol 934P, the gelling agent utilized in the investigation and assessment, exhibits good consistency and tolerable flow behavior. The best result was obtained from the organoleptic, physicochemical determination. Formulations F14–F18 displayed varying release patterns during in vitro evaluation, however formulation F15 demonstrated the most consistent and optimal outcomes. The acquired data demonstrated that a combination of 2% ethanol, 1.75% isopropyl myristate, and 74.5% propylene glycol as a concentration is promising to boost dimenhydrinate permeability from transdermal gel. Using the Carbopol 934P gelling agent, the other outcomes, such as the organoleptic and flow properties, were successfully and effectively attained. Conclusion: Compared to other combinations of permeation enhancing agents, the use of ethanol as a permeation enhancer in combination with isopropyl myristate and propylene glycol is superior. Additionally, carbopol is a promising gelling agent that can be used to make gel dosage forms.